Minority-carrier dynamics in β-gallium oxide probed by depth-resolved cathodoluminescence. (23rd September 2022) - Sugie, Ryuichi; Uchida, Tomoyuki
Abstract: The behavior of hole polarons in β -gallium oxide (Ga2 O3 ) has attracted significant attention. Depth-resolved cathodoluminescence (CL) was used to investigate the minority carrier dynamics in β -Ga2 O3 . First, a model describing CL intensity was proposed by considering the depth-dose function and surface recombination. A universal depth-dose function for β -Ga2 O3, which has the form of a third-degree polynomial, was presented based on Monte Carlo simulation by introducing a normalized depth, which is the depth normalized by the electron beam range. Second, two experimental approaches, plan-view and cross-sectional CL measurements, were applied to unintentionally doped β -Ga2 O3 (−201) wafers, and the experimental results were compared with those of the proposed model. The hole diffusion length was estimated to be within the range of 200–400 nm through the plan-view measurement, whereas a hole diffusion length of 250 nm was obtained through the cross-sectional measurement. The values were consistent with each other, and the model reproduced the experimental results well. This indicates that the nonequilibrium minority hole in the unintentionally doped β -Ga2 O3 is mobile and forms a 'weak' polaron. The reduced recombination velocity of the (−201) face was estimated to be approximately ten for the plan-view measurement, whereas that of ten or more was assumed for the cross-sectional measurement. No inconsistency was observed, but the low-energy plan-view measurement is considered more suitable for investigating the surface recombination velocity.